EPIDEMIOLOGI DAN PENGELOLAAN PENYAKIT LAYU BAKTERI PADA TANAMAN JAGUNG - Nurasiah Djaenuddin; Amran Muis (Badan Penelitian dan Pengembangan Pertanian, 2018)
Maize is one of the most important worldwide agricultural crops that their seed is considered a valuable international trading item. The seeds are mainly originated from United States, where the world most intensive development of new varieties occurs. Pantoea stewartii is a pathogenic bacteria of maize that occurs primarily in the US. Stewart wilt disease in maize caused by the bacterium Pantoea stewartii is become a new disease of maize in Indonesia. The stewart wilt disease was first reported in West Sumatra with the disease incidence of 1−15%. This paper discusses the epidemiology and control efforts of the bacterial stewart wilt disease in maize. Stewart wilt disease is a seed borne disease and it can transmitted by insect vector Chaetocnema pulicaria. P. stewartii has a wide host range including maize plant. In addition to maize plants, the pathogen also attacks sugarcane, sorghum, wheat, green beans, cucumbers, and several types of grasses. The abundant availability and wide range of its hosts, allows the pathogen to easily find the host to survive and develop. P. stewartii attacks maize in all stages of plant growth. The emergence of this disease on maize plant is mainly due to imported seeds from outside of Indonesia. Seed is the most suitable carrier media for pathogens to spread across its natural boundaries. One of the efforts to prevent the outbreak of the disease in Indonesia is to control its insect vectors. Several efforts that can be done to control the disease are environmental sanitation and by chemical pesticides with active ingredient such as imidacloprid, thiamethoxam, and clothianidin.Keywords: Maize, Pantoea stewartii, host plant, seed treatment AbstrakJagung merupakan salah satu komoditas pangan dan pakan penting dunia dan benihnya diperdagangkan secara internasional. Volume tertinggi perdagangan benih jagung berasal dari Amerika Serikat yang merupakan negara penghasil utama varietas unggul baru jagung di dunia. Pantoea stewartii adalah bakteri patogenik penting pada tanaman jagung, khususnya di Amerika Serikat. Penyakit layu stewart pada tanaman jagung disebabkan oleh bakteri Pantoea stewartii yang merupakan penyakit baru di Indonesia. Penyakit ini pertama kali dilaporkan di Sumatera Barat dengan insidensi 1−15%. Makalah ini membahas epidemiologi dan upaya pengendalian penyakit layu bakteri stewart pada tanaman jagung. Penyakit layu stewart merupakan penyakit tular benih dan tular serangga melalui vektor Chaetocnema pulicaria. P. stewartii memiliki inang yang luas, termasuk tebu, sorgum, gandum, kacang hijau, mentimun, dan beberapa jenis rumput-rumputan. Melimpahnya ketersediaan inang menjadikan patogen ini mudah dan cepat berkembang. Penyakit layu bakteri stewart pada tanaman jagung dapat berasal dari benih impor. Benih merupakan media pembawa penyakit yang paling efektif dan menyebar luas dengan melintasi batas alaminya. Salah satu upaya untuk mencegah wabah penyakit layu stewart ialah mengendalikan serangga vektor. Sanitasi lingkungan dan penggunaan pestisida berbahan aktif imidacloprid, thiamethoxam, dan clothianidin merupakan alternatif pengendalian.Kata kunci: Jagung, Pantoea stewartii, tanaman inang, perlakuan benih